PROJECT ACTIVITIES AS A FACTOR IN THE DEVELOPMENT OF HUMAN ABILITIES - Intizor Kamilovna Abdirimova (European Science Publishing, 2025)
This article describes the theoretical foundations of project activities, the emergence of the design method and the principles of its implementation in the education system. Several basic and specific features of the design method in improving the quality of education are also shown. It is explained that the design activity helps to make the final objective and clear conclusion in the formation of the student's personality and is important.
Keywords: Project, educational system, student, innovative technology, innovative approach, pedagogical technology, project activity, pedagogical psychology, pedagogical education.